Immune response in susceptible BALB/c mice immunized with DNA encoding Lipophosphoglycan 3 of Leishmania infantum. (December 2014) - Pirdel, L.; Zavaran Hosseini, A.; Rasouli, M.
Summary Visceral leishmaniasis is a serious parasitic infection that the development of an effective vaccine is necessary to control the disease. Lipophosphoglycan 3 (LPG3) is essential for the synthesis of glycoconjugates as parasite virulence factors. In this study, we evaluated the immunogenicity of Leishmania infantum LPG3 gene as a DNA vaccine against murine visceral leishmaniasis. For this purpose, BALB/c mice were immunized subcutaneously with the DNA encoding LPG3 either alone or in combination with recombinant heat shock protein 70 (rHSP70). Next, its immunogenicity and protective efficacy were evaluated in the immunized mice. The results showed a mixed Th1/Th2 response following immunization, which was associated with the production of both IFN‐γ and IL‐10 by splenocytes compared with control groups but did not lead to reduction in the splenic parasite burden. Serum levels of IgG antibody isotypes indicated no significant difference between the LPG3 DNA and the empty vector. In addition, the co‐administration of rHSP70 with the DNA vaccine offered no additive protective advantage on experimental infectious challenge. Thus, we propose to strengthen the immunogenic potential of L. infantum LPG3 in prime‐boost approach with a powerful adjuvant to elicit a robust parasite‐specific protective Th1 response.